Biosorptive removal of Pb(II) from aqueous solution by dried water hyacinth (Eichhornia Crassipes) roots - Zuñiga, Anna Veronica O. (2012)
In this study, adsorption of Pb(II) from aqueous solutions byd dried water hyacinth (Eichhornia crassipes) roots was investigated under batch mode. Scanning Electron Microscopy (SEM) images of dried water hyacinth roots revealed an irregular rough surface and porous structure, while Fourier Transform Infrared (FTIR) spectra revealed the presence of carboxyl and hydroxyl functional groups. All epxeriments showed that the adsorption capacity and rate of adsorption of Pb(II) on dried water hyacinth roots increased with the temperature (25deg.C-60deg.C), pH (2-5) and initial concentration (10-100 mgL-1). A 99.46% removal of 50 mgL-1 Pb(II) was achieved by 0.10 g dried water hyacinth roots (solution pH 5. 26 +/-1 deg.C, 200 rpm shaking speed, for 60 minutes). it was found that experimental data fitted the pseudo-second order kinetic model (R2=0.99~1.0), indicating chemisorption as the rate-limiting step in the adsorption. The equilibrium data showed better agreement with Freundlich isotherm model (r2=0.83~0.99) which indicated adsorption in heterogeneous layer. at higher pH (4-5) and temperature (60 deg.C), Langmuir model showed a better fit, and revealed that dried water hyacinth roots also have large monolayer adsorption capacity and high affinity for Pb(II) at this conditions. The calculated experimental values of energy changes associated with the adsorption (Ea=18.23 KJmol-1 AH=13.52 KJmol-1, As=146.25 Jmol-1K-1, and Ag=-30.09 to -35.25 KJmol-1) showed the spontaneous and endothermic nature of adsorption, which is a combination of both physiosorption and chemisorption. This study confirms that dried water hyacinth root is an excellent low-cost biosorbent for the removal of Pb(II) from aqueous media.
Thesis (M.S. Environmental Engineering)--University of the Philippines, Diliman.
Keywords: Water hyacinth